2013
DOI: 10.1179/1743132812y.0000000116
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents global cerebral ischemia-induced decrease in lipid content

Abstract: Our experiments suggest that lipid metabolism is important for development of ischemic damage and indicate that RSV treatment 7 days prior to ischemia may prevent membrane lipid loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…It possesses a wide range of biological effects including anti-apoptotic (9,10), anti-oxidative (11), anti-inflammatory (12) and anti-carcinogenic properties (13). Resveratrol has been reported to exhibit neuroprotective effects in the models of numerous diseases, such as cerebral ischemia (14,15), kainic acid-induced excitotoxicity (16), Huntington’s disease (17), Parkinson’s disease (18) and Alzheimer’s disease (19). However, data evaluating the effects of resveratrol in VaD are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It possesses a wide range of biological effects including anti-apoptotic (9,10), anti-oxidative (11), anti-inflammatory (12) and anti-carcinogenic properties (13). Resveratrol has been reported to exhibit neuroprotective effects in the models of numerous diseases, such as cerebral ischemia (14,15), kainic acid-induced excitotoxicity (16), Huntington’s disease (17), Parkinson’s disease (18) and Alzheimer’s disease (19). However, data evaluating the effects of resveratrol in VaD are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The results concerning the use of RSV transported in RO represent a promising therapeutic alternative for the treatment of symptoms related to several diseases, including FM, as we have presented here. The therapeutic approach of RO-combined RSV is reinforced by data published by other groups, in which the effects of the RSV were improved by lipid core nanocapsules [ 30 , 54 ].…”
Section: Discussionmentioning
confidence: 97%
“…Brain lipid metabolism was studied by bilateral common carotid artery ligation, a model for chronic cerebral hypoperfusion, which showed that dysbolism might be caused by compensatory secretory phospholipase A (2)‐mediated vasodilation . Another experiment used compound to prevent membrane lipid loss and suggested that lipid metabolism was important for the development of ischemic damage . A recent study suggested that cell cycle modulation resulted in neuroprotection in ischemia, which was mediated at least in part through inhibition of microglia proliferation and production of inflammatory cytokines .…”
Section: Discussionmentioning
confidence: 99%